Prevalence and Genotyping of Anaplasma phagocytophilum Strains from Wild Animals, European Bison (Bison bonasus) and Eurasian Moose (Alces alces) in Poland - Anna W. Myczka; Stanisław Kaczor; Katarzyna Filip-Hutsch; Michał Czopowicz; Elwira Plis-Kuprianowicz; Zdzisław Laskowski (Animals, 2022)
Wild large ungulates, like European bison (Bison bonasus) and Eurasian moose (Alces alces), form an important part of the circulation of Anaplasma phagocytophilum, a Gram-negative, intracellular, tick-transmitted bacterium, in the natural environment. Bison and moose tissue samples were subjected to 16S rDNA, groEL and ankA partial gene marker amplification with specific primers using various variants of PCR. Out of 42 examined individuals, Anaplasma sp. were detected in 4/13 Eurasian moose (31%) and 7/29 European bison (24%). In addition, 12 groEL and 5 ankA partial gene positive samples were obtained from the examined animals. The phylogenetic analysis of the groEL partial gene classified samples from European bison to ecotype I, and samples from Eurasian moose to ecotype I and II; the analysis of the ankA partial gene assigned the samples to clusters I and IV. This study extends knowledge about A. phagocytophilum in wild large ungulates in Poland. This is the first report about the occurrence of Anaplasma sp. in one of the largest populations of free living European bison in the world. Our findings confirm that strains of A. phagocytophilum from Bison bonasus and Alces alces may constitute a natural reservoir of pathogenic HGA Anaplasma strains.